Gender and Justice in Jordan : Women, Demand, and Access - Prettitore, Paul Scott (World Bank, Washington, DC, 2014)
Two key dimensions on access to justice sector services in Jordan are poverty and gender. The gender dimension to accessing formal justice sector services, namely court and lawyer services is anchored in the reality that women and men in Jordan demonstrate different needs and priorities for services, and face different obstacles in accessing them. Jordan demonstrates different needs and priorities for services, and face different obstacles in accessing them. Understanding these differences has been considerably enhanced by disaggregation of data from the statistical survey on the volume of demand for legal aid (LAS) by gender. This data is complimented by analysis of the caseload of the Justice Center for Legal Aid (JCLA), which is arguably Jordan's largest legal aid provider and whose beneficiaries are predominately women. Justice sector officials and policy-makers now have better empirical data to inform reforms aimed at improving service delivery. This data can also be used to target services to better support broader objectives of increased economic participation and agency for women, and shed light on how the justice sector can impact inclusion and equality. Enhancing public information and developing self-help (pro se) representation mechanisms may help in increasing access to services and make services more financially sustainable. Such initiatives may prove particularly useful in personal status cases, where the convergence of justice and gender dimensions appears the most comprehensive, and perhaps where greater impact on women's development can be obtained.